THE EFFECTIVENESS NUMBER OF BAFFLE BLOCKS TO REDUCE ENERGY IN TUKUTAHA TRANSITION CHANNELS - Agustina Nababan; Nadjadji Anwar; Wasis Wardoyo (Institut Teknologi Sepuluh Nopember (ITS), 2021)
One of the causes of damage to the weir structure is scouring that can accur along the weir channel. Scouring occurs due to the high flow velocity and high specific energy. One of the methods used to reduce specific velocity and energy is by installing baffle blocks in parts that have high velocity and energy. The addition of baffle blocks is carried out at a place that has a high velocity, namely the transition channel. To see the effect of baffle block variation on velocity and energy, a study was conducted. The study was conducted with four baffle block models type. Model type 0 is a model with the same assumptions as of the existing one. model type 1 is designed based on the planning of The Colorado State University (CSU) rigid boundary basin. Model type 2 is designed by reducing the number of baffle blocks from the initial design of 102 baffles to as many as 75 baffles. while the 3 channel model type transitions without baffle blocks. Based on the percentage of energy loss analysis in the transition channel, Model type 0 can reduce energy greater than others models. At maximum discharge, the model type 0 has an energy loss of 10.821% greater than the model type 1, 14,889% greater than the model type 2, and 33.02% greater than the model type 3.